(untitled) (Al-NASR, 2025)
Imam al-Ghazali (1058–1111), known as “Hujjat al-Islam,” was a monumental Muslim theologian, jurist, philosopher, and Sufi whose intellectual legacy shaped Islamic thought in theology, philosophy, law, spirituality, and ethics. Born in Tus, he received his education under Imam al-Haramayn al-Juwayni in Nishapur and later rose to great prominence as a teacher at the Nizamiyya of Baghdad. His major works—especially Ihya’ ‘Ulum al-Din, Kimiya-e-Sa‘adat, Tahafut al-Falasifah, al-Munqidh min al-Dalal, and Maqasid al-Falasifah—combine deep spiritual insight, ethical reform, philosophical critique, and practical guidance for believers. Kimiya-e-Sa‘adat, his celebrated Persian masterpiece, summarizes the essence of Islamic spirituality through four themes: knowledge of God, purification of the soul, moral excellence, and righteous social conduct. Ghazali’s methodological balance between Qur’an, Sunnah, logic, philosophy, and Sufism makes his work timeless, offering Muslims a comprehensive path toward spiritual purification, ethical refinement, and success in this world and the Hereafter.